The Criticism of Artistic Aesthetics of Literary Texts - سوسن جبری (مطالعات زبانی و بلاغی)
The subject of this study is a suggestion for the analysis of literary analysis. Its aim is the implication of the methodological methods based on the objective data in the literary criticism in order to avoid any biased criticism. In this combinative method, first by analyzing texts in structural linguistics, language foregrounding in texts is compiled in order to achieve objective, qualitative and convincing data for the analysis of the principles, and then with analysis and classification, investigation on highlighting language, the presence of the elements of artistic beauty like unity, harmony, proportion, conformity, symmetry, discipline and dynamism will be displayed and discovered in the text. In this way artistic beauty whose principle is common in all the arts is investigated as well in literary texts in order to display the other aspects of the beauty in the literary text.